ANALISIS LINGKUNGAN KERJA TERHADAP KINERJA - Kusumah, Adie Irwan (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2021)
The discomfort felt so far by employees of the Public Works Office and Cirebon City Space Stewards has a direct impact on the performance of employees who have not beenmaximized, so the author is interested in conducting research conducted in the form of thesis with Environmental Analysis of Work On The Performance of Employees of the Public Works Office and Cirebon City Space Stewards. The research method used is descriptive research analysis method,while the sampling technique used in this study is a simple random sampling of 60 respondents. Data collection techniques are conducted using literature studies, observations, questionnaires and documentation studies. Data analysis on the influence between free variables i.e. work environment with variables tied to employee performance. The result is calculated t value of 14,429 while in table t at df 60 is 1,671; so tcount > table t or 14,429 > 1,671. This means that H0 is rejected and Ha is accepted, which means there isa significant influence on the performance of employees at the Cirebon Public Works And Space Stewardship Office, thus the hypothesis is proven. While the correlation coefesien value is 0.884 while the determining coefesien value obtained is 0.782 or 78.20%. This percentage of the influence of work environment variables on employee performance is 78.20%. While the remaining 21.80% was influenced by other variables not studied in this study. Keyword : : Work Environment, Employee Performance